Stemming Machine Saves Kennecott Time and Money in Blasting Operations (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1976)
The manpower and time involved in primary blasthole stemming at Kennecott Copper Corp.'s Bingham Canyon mine have been reduced considerable through the use of a mobile stemming machine invented y three mine employees. The patented machine, developed 2% years ago at an estimated cost of $5000 for two units, is the brainchild of Thomas R. Carlson, mine plant superintendent; Alvin J. McIntosh, drilling and blasting engineer; and Jay K. Buehler, field repair general foreman. According to McIntosh, the machine has been well received by the mine employees, who have been relieved of the tedious task of hand shoveling drill cuttings into the blastholes. It is estimated that the stemming machine has saved the mine approximately $25,000 per year in overtime and regular labor costs.